Shari’ah compliance safety for Malaysia homestay Muslim travellers - Wan Ibrahim, Irwan Khazani; Hashim, Khairusy Syakirin Has-Yun (International Institute for Halal Research and Training (INHART), International Islamic University Malaysia, 2023)
Muslim travellers are gradually showing interest in travelling to Muslim-friendly countries, specifically Malaysia. Malaysia is one of the few Islamic-viewing countries offering unique accommodation via the local homestay experience. However, the regulations set by the local authority are loosely enforced, especially regarding homestay guests' safety. Interpretations of safety are largely contributed only by each registered local homestay, with only minor guidelines provided by the local authority. It is also unclear whether the safety measures of homestays in Malaysia comply with Shari’ah principles. For example, under the official guidelines, insurance is to be adopted by homestays for the safety of the guest. However, Muslim travellers do not have a choice between Shari’ah and non-Shari’ah policies. When it comes to insurance policies, it is up to the homestay owner to provide Shari’ah-compliant or non-compliant coverage. Therefore, the article aims to explore whether the safety measures of homestays in Malaysia comply with Shari’ah principles and suggests ways to address these issues. Findings indicate that homestays' current level of safety and security in Malaysia is not standard since MOTAC’s guidelines are too general and not curated for each homestay. Suggestions in the form of a flow chart were put forward to address concerns about safety and security and to ensure compliance with Shari’ah principles.